Enhancements of Triethanolamine CO2 Absorption Rate and Degradation in the Presence of Nickel Nanoparticles Catalysts - Harold W. Orendi; Kevin Joby; Lidija Šiller (Atmosphere)
Here, the catalytic and degradation effect of nickel nanoparticles (NiNPs) on triethanolamine (TEA) with CO2 at 20 °C and 50 °C and a range of TEA concentrations (3–30 wt%) was studied. We show that TEA absorption rate of CO2 can be enhanced with NiNPs, the maximum enhancement was 8.3% when compared to a control solution found at 50 °C with 30 wt% TEA alone. Additionally, the time for TEA to be fully loaded with CO2 is reduced; compared to the control, NiNPs enhanced solutions were up to 26.3% faster. Also, to the best of our knowledge, this is the first time the degradation of TEA with NiNPs has been studied. TEA was subject to both oxygen (30 wt%, 55 °C, 0.35 L/min of air, 0.4 molCO2/molTEA, 7.5 mL/min of CO2) and thermal degradation with and without NiNPs (30 wt%, 0.5 molCO2/molTEA, 135 °C). In both degradation experiments, surprisingly, there was no significant difference in TEA degradation in the presence of NiNPs. At high temperature (135 °C), the solution lost 19.2% and 20.3% of the original TEA, with and without NiNPs, respectively. In the presence of oxygen, the solution lost 30.5% and 33.6% of the original TEA, with and without NiNPs, respectively. This indicates that TEA or its mixture with other amines and NiNPs could improve post-combustion CO2 capture.